2013
DOI: 10.1038/cmi.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement and expression of the immunoglobulin μ-chain gene in human myeloid cells

Abstract: Immunoglobulin (Ig), a characteristic marker of B cells, has been reported to be expressed in epithelial cells, with a suggested role in their growth and survival. We have previously reported that IgG heavy chain is expressed in acute myeloid leukemia (AML), but not in the monocytes or neutrophils from patients with non-hematopoietic neoplasms or healthy controls. In the present study, we assessed IgM heavy chain expression and repertoire in human myeloid cells. We detected V Hm DJ Hm rearrangement and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 23 publications
2
41
1
Order By: Relevance
“…We also have shown that IgG can be expressed in myeloblasts, and it has unique VDJ rearrangements and has undergone somatic hypermutation 8‐10 . Furthermore, AML‐derived immunoglobulin has functional significance and is involved in proliferation, apoptosis, and migration of leukemic cells 8‐10 . These findings suggest that AML‐derived immunoglobulin may have a role in AML pathogenesis and progression, and could serve as a novel marker for monitoring residual disease and developing target therapy.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…We also have shown that IgG can be expressed in myeloblasts, and it has unique VDJ rearrangements and has undergone somatic hypermutation 8‐10 . Furthermore, AML‐derived immunoglobulin has functional significance and is involved in proliferation, apoptosis, and migration of leukemic cells 8‐10 . These findings suggest that AML‐derived immunoglobulin may have a role in AML pathogenesis and progression, and could serve as a novel marker for monitoring residual disease and developing target therapy.…”
Section: Introductionmentioning
confidence: 72%
“…Although it was once presumed that B lymphocytes and plasma cells are the only sources of immunoglobulin, in the past decades it has been reported that immunoglobulin is expressed in many types of neoplastic epithelial cells 2‐5 and non‐neoplastic cells 6,7 . We also have shown that IgG can be expressed in myeloblasts, and it has unique VDJ rearrangements and has undergone somatic hypermutation 8‐10 . Furthermore, AML‐derived immunoglobulin has functional significance and is involved in proliferation, apoptosis, and migration of leukemic cells 8‐10 .…”
Section: Introductionmentioning
confidence: 97%
“…In studies of AML, genetic analysis indicates that the immunoglobulin heavy chains genes have undergone VDJ rearrangement in 40–50% of cases and that the expression of the VDJ recombinase associated proteins RAG1 and RAG2 was also detectable in approximately 50% of cases [ 136 , 228 ]. More recent data confirms that VDJ recombination had occurred in the AML myeloblasts of 50% of patients and that there was also limited evidence of somatic hypermutation occurring [ 229 ]. In keeping with the observation that VDJ rearrangement is a common event in haematopoietic stem cells destined to proceed towards myeloid differentiation, evidence of significant level of earlier VDJ recombination but not somatic hypermutation are found in monocytes and neutrophils from healthy donors [ 229 ].…”
Section: Discussionmentioning
confidence: 85%
“…More recent data confirms that VDJ recombination had occurred in the AML myeloblasts of 50% of patients and that there was also limited evidence of somatic hypermutation occurring [ 229 ]. In keeping with the observation that VDJ rearrangement is a common event in haematopoietic stem cells destined to proceed towards myeloid differentiation, evidence of significant level of earlier VDJ recombination but not somatic hypermutation are found in monocytes and neutrophils from healthy donors [ 229 ]. It is possible that this presence of VDJ activity and the associated pro-apoptotic processes may be linked to the high degree of sensitivity in the production of these cells seen during chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Following the observation that IgK transcripts were upregulated in the aged LT-HSC population, and indeed throughout the myeloid progenitor (Fig 2M), we used the long read data to determine that the IgK arising from the LT-HSC population in aged mice consisted not just of "germline" IgK, as previously reported 12 , but fully VDJ-recombined transcripts (Fig 2N, Supplementary Fig 3). While unprecedented, there is an increasing body of evidence that the expression of recombined Ig molecules in non-lymphoid cells is possible [19][20][21] , often in age-related diseases such as acute myeloid leukemia 22 .…”
Section: Main Textmentioning
confidence: 99%